2013
DOI: 10.1177/1049731513510409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Sexual Abuse Prevention Education for Chinese Preschoolers

Abstract: Objectives: The purpose of this study was to test the feasibility of a sexual abuse prevention education in a sample of Chinese preschool children in Beijing, China. Method: One hundred and fifty preschool children were randomly assigned to either the intervention group (N ¼ 78) or the wait-list control group (N ¼ 72). Children were posttested on sexual abuse prevention knowledge and self-protection skills gains. Results: Following program participation, preschool children in the intervention group demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 42 publications
1
28
0
4
Order By: Relevance
“…Previous research provides strong evidence to support that school-based prevention can be helpful in preventing CSA as a whole (Finkelhor, 2007;Topping & Barron, 2009), and that beginning primary CSA prevention with preschoolaged children is important and feasible (Berrick & Barth, 1992;Finkelhor, 2007;Wurtele & Owens, 1997;W. Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research provides strong evidence to support that school-based prevention can be helpful in preventing CSA as a whole (Finkelhor, 2007;Topping & Barron, 2009), and that beginning primary CSA prevention with preschoolaged children is important and feasible (Berrick & Barth, 1992;Finkelhor, 2007;Wurtele & Owens, 1997;W. Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, Wurtele and Owens (1997) employed data from five studies with preschool-aged children and found that preschool-aged children who had participated in a 5-day Behavioral Skills Training (BST) program had significant improvement in their selfprotection skills. In another recent study in China, W. Zhang et al (2014) found that Chinese preschool-aged children increased their scores on knowledge of sexual abuse and skills related to CSA prevention after participating in a childdirected prevention program.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings suggest that it is feasible to implement the sexual abuse prevention education with Chinese pre-schoolers [10]. Another finding shown based on analysis of 3 areas in Chinese, it was found that there was a lack of connection between theoretical models and concrete preventive interventions [11]. Another experimental research conducted prevention with three conditions: (1) in person training, (2) web-based training, or (3) wait list control.…”
Section: Introductionmentioning
confidence: 99%